The Media Image of Afghan Women as Reflected by News Websites in 2021: an Analytical Study of Russia Today site - Salman, Haneen Saad (ALBAHITH ALALAMI, 2022)
International news websites, including Russia Today, pay special attention to the media image of Afghan women, especially after the Taliban movement took control of Afghanistan. Therefore, it was necessary to know the image of the Afghan woman, the fate of the rights she acquired in recent years, and the transformations that affected her after the Taliban took control of the government, and studied them on international news sites, specifically Russia Today.          The researcher summarized the problem of this study in the following question: What is the media image of the Afghan woman on the Russia Today news site?          The researcher followed the survey method in order to reach the results, the most important of which were: The determinants of the media image of Afghan women lie in the journalistic treatment provided by the contact person on the Russia Today website in focusing on highlighting the international media and political perception of the situation of Afghan women and on raising international concerns about the future of Afghan women Under the rule of the Taliban, as it is threatened with exclusion from society, and the demand for its rights through the demands of states, international organizations and activists.